Construction of rational regimes in motor activity of children aged 3-4 years in pre-school educational institutions of various types - N.V. Moskalenko; A.V. Poliakova; T.V. Sidorchuk (H.S. Skovoroda Kharkov National Pedagogical University, 2018)
Purpose: to develop rational regimes of physical activity and to determine their influence on the physical condition of children aged 3-4 years attending pre-school institutions of various types. Material: the research was carried out in pre-school educational institutions of various types in the city of Dnepr (Ukraine) (№ 282, combined type, № 192, sanatorium type, № 28, compensatory type, № 244 and № 404, general development). One hundred and eighty-five children took part in the research, 103 of them were 3-year-olds and 82 - preschoolers of 4-year-old age. Control and experimental groups were formed in each age group in kindergartens of a certain type. The control group consisted of 91 children, the experimental group - 94. In the study we used measurements of anthropometry, pulsometry, spirometry, functional tests. The obtained results were processed by independent t-test to evaluate differences between groups. Results: the functional conditions of the children's study of the experimental groups (boys and girls) have positive changes in the spirometry indices, respiration rates, pulsometry, Ruffier index with a significant difference with the control groups (p<0,05). In addition, in the course of our research, the parameters of the motor activity of children 3-4 years were determined on the base of pacing, while carrying out various organizational forms of physical education. These indicators can be oriented towards the development of a rational motor regimen for younger preschool children. Conclusions: the proposed regimes and forms of motor activity can be used in the organization of physical education of children in pre-school educational institutions of different types for the improvement of morphofunctional indices and physical activity.